A retrospective study examining the adverse effect of childhood abuse among adult psychiatric service users in Britain. (15th March 2021) - Mantovani, Nadia; Smith, Jared
Abstract: The long‐term effects of childhood abuse have been well studied though the effects of abuse of specific types in adult psychiatric service users are less known. This study aimed to assess the association between childhood abuse and the development of harmful social and behavioural outcomes among adult psychiatric service users. Adult psychiatric service users were accessed from secondary mental health services in South London. A retrospective analysis was conducted of a randomly selected sample of 342 mental health records. Chi‐square tests and logistic regression models were used to examine associations between childhood abuse – sexual abuse, physical abuse and psychological/emotional abuse – and health and behavioural outcomes. This study identified that 109 (31.8%) psychiatric service users had some history of childhood abuse and more often presented with high‐risk or severe behaviours. Sexual abuse in childhood was linked with social isolation related to loss of friends (odds ratio (OR) = 2.68, P  < 0.01), risky behaviours such as binge drinking (OR = 2.15, P  < 0.05) and self‐harming (OR = 2.86, P  < 0.01), while childhood physical abuse was associated with drug abuse in adulthood (OR = 1.88, P  < 0.05). Revictimization (adult domestic violence) also impacted on service users' quality of life in terms of loss of housing (OR = 2.21, P  < 0.05) and loss of friends/family contact (OR = 2.73, P  < 0.01). These findings suggest childhood abuse may play an important role in shaping risk and vulnerability for mental health problems across a lifespan. In acute mental health services, the incorporation of a trauma‐informed nursing care model is necessary to generate a shift in culture in the delivery of care.